Incorporation of Brentuximab Vedotin in the Treatment of Lymphoma: Current Evidence and Potential Use in Indonesia - Ibnu Purwanto (Acta Interna The Journal of Internal Medicine, 2020)
Although scientific advances have resulted in significantly improved survival among lymphoma patients, certain subsets of lymphoma patients still have poor prognosis, which includes relapsed and treatment refractory patients. Brentuximab vedotin, an anti-CD30 targeted therapy has shown remarkable results given in both Hodgkin and non-Hodgkin lymphoma, even in cases without CD30 expression. Unfortunately, evidence of its effectiveness in Indonesian patient is still limited as there is only 1 case report of such subject published.Conclusion: Brentuximab vedotin, an anti-CD30 targeted therapy presents as an effective therapeutic option for relapsed and treatment refractory lymphoma patients.